The effect of pre‐existing mental health comorbidities on the stage at diagnosis and timeliness of care of solid tumor malignances in a Veterans Affairs (VA) medical center. (9th June 2015) - Wadia, Roxanne J.; Yao, Xiaopan; Deng, Yanhong; Li, Jia; Maron, Steven; Connery, Donna; Gunduz‐Bruce, Handan; Rose, Michal G.
<x xml:space="preserve">Abstract</x> In veterans with and without pre‐existing mental health comorbidities (MHC), no significant difference was seen in the stage at diagnosis or timeliness of care for solid tumor malignancies at the Veterans Affairs Connecticut Medical Center. This is counter to multiple prior studies of cancer patients with MHC and may be explained by the VHA's integration of mental health care into the medical care.<boxed-text content-type="graphic" id="cam4483-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>